2008
DOI: 10.1210/en.2007-1506
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Hypothalamic Protein Tyrosine Phosphatase Improves Insulin and Leptin Resistance in Diet-Induced Obese Rats

Abstract: Protein tyrosine phosphatase (PTP1B) has been implicated in the negative regulation of insulin and leptin signaling. PTP1B knockout mice are hypersensitive to insulin and leptin and resistant to obesity when fed a high-fat diet. We investigated the role of hypothalamic PTP1B in the regulation of food intake, insulin and leptin actions and signaling in rats through selective decreases in PTP1B expression in discrete hypothalamic nuclei. We generated a selective, transient reduction in PTP1B by infusion of an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
92
0
16

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 40 publications
6
92
0
16
Order By: Relevance
“…PTP1B is known as a nonreceptor type tyrosine phosphatase and negatively regulates insu lin and leptin signaling (11,12). The genetic deletion or pharmacological intervention of PTP1B is known to have antidiabetic and antiobesity effects by amplifying insulin and leptin signaling, respectively (13,14). KY 201 was previously reported to reduce plasma glucose and triglyceride (TG) levels more effectively than rosi glitazone in KKA y mice, even though both compounds have similar human PPARg agonistic activities in COS1 cells (10), which suggests the involvement of PTP1B inhibition in its insulinsensitizing effects.…”
Section: Introductionmentioning
confidence: 99%
“…PTP1B is known as a nonreceptor type tyrosine phosphatase and negatively regulates insu lin and leptin signaling (11,12). The genetic deletion or pharmacological intervention of PTP1B is known to have antidiabetic and antiobesity effects by amplifying insulin and leptin signaling, respectively (13,14). KY 201 was previously reported to reduce plasma glucose and triglyceride (TG) levels more effectively than rosi glitazone in KKA y mice, even though both compounds have similar human PPARg agonistic activities in COS1 cells (10), which suggests the involvement of PTP1B inhibition in its insulinsensitizing effects.…”
Section: Introductionmentioning
confidence: 99%
“…Positive energy balance and obesity pathogenesis are thought to result from defects in inhibitory feedback signaling to the CNS (including neuronal insulin and leptin resistance and impaired nutrient sensing) (44,45). We hypothesized that increases in NPY tone within these neural circuits may contribute to dyslipidemia in addition to obesity.…”
mentioning
confidence: 99%
“…In all three models, the expression of 72k-5ptase was significantly increased in both skeletal muscle and white adipose tissue. Interestingly, a number of studies have shown that PTP1B, a tyrosine phosphatase known to exert an important regulatory role in insulin and leptin signaling, is increased in obesity, and this increased expression is thought to be one of the main mechanisms connecting increased adiposity to insulin and leptin resistance (Bence et al 2006, Picardi et al 2008. Thus, we suspect that the increased expression of 72k-5ptase in obesity is yet another mechanism promoting resistance to insulin and leptin.…”
Section: Discussionmentioning
confidence: 92%